Dyeing of Tussah Silk with Reactive Dyes: Dye Selection, Dyeing Conditions, Dye Fixation Characteristics, and Comparison with Mulberry Silk - Yingjie Yu; Rencheng Tang (Molecules, 2024)
Tussah silk is one of the most widely used wild silks. It is usually dyed with acid dyes, despite the shortcoming of poor wet fastness. Reactive dyeing is a good solution to this problem. In our work, sulfatoethylsulfone (SES), sulfatoethylsulfone/monochlorotriazine (SES/MCT), monochlorotriazine (MCT), and bis(monochlorotriazine) (Bis(MCT)) dyes were used to dye tussah silk. All of these dyes showed lower exhaustion and fixation on tussah silk than on mulberry silk under alkaline conditions. Among them, SES dyes were more applicable, with a fixation of 70–85% (at 4%owf dye) at 90 °C when using sodium bicarbonate as an alkali. SES dyes also showed a rapid fixation speed. The dyeing of tussah silk required lower sodium bicarbonate dosage, the use of more neutral electrolytes, and a higher dye quantity to achieve deep effects compared to mulberry silk. Dyed tussah silk displayed lower apparent color depth and brilliance than dyed mulberry silk. The neutral boiling dyeing of tussah silk with SES dyes exhibited higher exhaustion, higher fixation (82–92% at 4%owf dye), and a slower fixation speed compared with alkaline dyeing. Furthermore, in this dyeing method, SES dyes showed higher and more efficient fixation on tussah silk than on mulberry silk. All dyed tussah silk had excellent color fastness to soaping.